Local partial depletion of CD11b+ cells and their influence on choroidal neovascularization using the CD11b‐HSVTK mouse model. Issue 7 (14th March 2018) - Brockmann, Claudia; Kociok, Norbert; Dege, Sabrina; Davids, Anja‐Maria; Brockmann, Tobias; Miller, Kelly R.; Joussen, Antonia M.
Abstract: Purpose: To assess the influence of retinal macrophages and microglia on the formation of choroidal neovascularization (CNV). Therefore, we used a transgenic mouse (CD11b‐HSVTK) in which the application of ganciclovir (GCV) results in a depletion of CD11b + cells. Methods: We first investigated if a local depletion of CD11b + macrophages and microglia in the retina is feasible. In a second step, the influence of CD11b + cell depletion on CNV formation was analysed. One eye of each CD11b‐HSVTK mouse was injected with GCV, and the fellow eye received sodium chloride solution (NaCl). Cell counting was performed at day 3 and 7 (one injection) or at day 14 and 21 (two injections). Choroidal neovascularization (CNV) was induced by argon laser and analysed at day 14. Results: The most effective CD11b + cell depletion was achieved 7 days after a single injection and 14 days after two injections of GCV. After two injections of GCV, we found a significant reduction of CD11b + cells in central (52 ± 23.9 cells/mm 2 ) and peripheral retina (53 ± 20.6 cells/mm 2 ); compared to eyes received NaCl (216 ± 49.0 and 210 ± 50.5 cells/mm 2, p < 0.001, respectively). Regarding CNV areas, no statistical significance was found between the groups. Conclusion: The CD11b‐HSVTK mouse is a feasible model for a local depletion of CD11b + cells in the retina. Nevertheless, only a partial depletion of CD11b + cells could be achieved compared to baseline data without any intravitreal injections. Our results did not reveal a significant reduction in CNV areas. In the light of previous knowledge, the potential influence of systemic immune cells on CNV formation might be more relevant than expected.